2017
DOI: 10.1371/journal.pone.0188383
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent abnormalities in pulmonary arterial compliance after heart transplantation in patients with combined post-capillary and pre-capillary pulmonary hypertension

Abstract: BackgroundThe hemodynamic definitions of pulmonary hypertension (PH) in left heart disease have recently been refined to better match the characteristics required to reflect the presence of pulmonary vascular disease. Accordingly, we tested the hypothesis that abnormalities in the stiffness of pulmonary circulation would persist after heart transplantation in patients with combined post-capillary and pre-capillary PH (Cpc-PH) in contrast to those with isolated post-capillary PH (Ipc-PH).MethodsWe retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
4
7
0
2
Order By: Relevance
“…23,26,27 The results of the present study are in line with previous studies as we found resting LV-filling and RV-filling pressures within the normal range in most patients. Studies of invasive haemodynamics demonstrate that resting LV and RV filling pressures tend to normalize in most HTx patients during the first months after surgery, whereas pulmonary arterial compliance remains reduced.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…23,26,27 The results of the present study are in line with previous studies as we found resting LV-filling and RV-filling pressures within the normal range in most patients. Studies of invasive haemodynamics demonstrate that resting LV and RV filling pressures tend to normalize in most HTx patients during the first months after surgery, whereas pulmonary arterial compliance remains reduced.…”
Section: Discussionsupporting
confidence: 92%
“…Studies of invasive haemodynamics demonstrate that resting LV and RV filling pressures tend to normalize in most HTx patients during the first months after surgery, whereas pulmonary arterial compliance remains reduced. 23,26,27 The results of the present study are in line with previous studies as we found resting LV-filling and RV-filling pressures within the normal range in most patients. However, the haemodynamic response to exercise is clearly abnormal in HTx patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The second mechanism is pulmonary arterial vasoconstriction and remodelling associated with increased pulmonary vascular resistances (PVR) partly due to an imbalance between a decreased nitric oxide (NO) availability and an increased endothelin expression, as described in the ‘mitral lung’ . In this case, reversibility of PH is uncertain, even after restoring normal left‐heart haemodynamics …”
Section: Introductionmentioning
confidence: 99%
“…14 In this case, reversibility of PH is uncertain, even after restoring normal left-heart haemodynamics. 15 Chronic PH induces right ventricular (RV) remodelling and might lead to RV failure, which has been shown to be an important prognostic factor in HF. 10,[16][17][18][19] At the late stage of HF, an elevated PVR has been considered a contraindication to heart transplantation as it may induce RV graft failure.…”
Section: Introductionmentioning
confidence: 99%